Retinal neurovascular coupling in diabetes - Garhöfer, Gerhard (2021)
Neurovascular coupling, also termed functional hyperemia, is one of the physiological key mechanisms to adjust blood flow in a neural tissue in response to functional activity. In the retina, increased neural activity, such as that induced by visual stimulation, leads to the dilatation of retinal arterioles, which is accompanied by an immediate increase in retinal and optic nerve head blood flow. According to the current scientific view, functional hyperemia ensures the adequate supply of nutrients and metabolites in response to the increased metabolic demand of the neural tissue. Although the molecular mechanisms behind neurovascular coupling are not yet fully elucidated, there is compelling evidence that this regulation is impaired in a wide variety of neurodegenerative and vascular diseases. In particular, it has been shown that the breakdown of the functional hyperemic response is an early event in patients with diabetes. There is compelling evidence that alterations in neurovascular coupling precede visible signs of diabetic retinopathy. Based on these observations, it has been hypothesized that a breakdown of functional hyperemia may contribute to the retinal complications of diabetes such as diabetic retinopathy or macular edema. The present review summarizes the current evidence of impaired neurovascular coupling in patients with diabetes. In this context, the molecular mechanisms of functional hyperemia in health and disease will be covered. Finally, we will also discuss how neurovascular coupling may in future be used to monitor disease progression or risk stratification.